2021
DOI: 10.1080/14786419.2021.2005050
|View full text |Cite
|
Sign up to set email alerts
|

Chemical components of Aconitum barbatum var. puberulum and their cytotoxic and antibacterial activities

Abstract: Nineteen compounds, including seventeen alkaloids O-methylarmepavine (1), (S)-6-methoxy-1-(4-methoxybenzyl)-2-methyl -1,2,3,4-tetrahydroisoquinolin-7-ol (2), (+)-(IR,laR)la-hydroxymagnocurarin (3), (6R,6aS,P)-(+)-corydine (4), (+)-N-methyllaurotetanine (5), magnoflorine (6), 3-hydroxy-1,2-dimethoxy-5-methyl-5H-dibenzoindol-4-one (7), imperialine ( 8), crispine B (9), (S)-1-(3-methoxyphenyl)-N-methylpropan-2-amine (10), methyl 2-(acetamino)benzoate (11), 2-carboxyoxanilic acid methylester (12), 4-[2-(methoxycar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…On the basis of the comprehensive analysis of spectroscopic data from high resolution electrospray ionization mass spectra (HRESIMS), 1D/2D nuclear magnetic resonance (NMR) spectra, ultraviolet (UV) spectra, and comparison with the references, four previously undescribed compounds were named Indusiataines A–D ( 1 – 4 ). Fourteen known compounds were elucidated to be 5-(Methoxymethyl)-1 H -pyrrole-2-carbaldehyde ( 5 ) [ 21 ], nicotinic acid ( 6 ) [ 22 ], dibutyl phthalate ( 7 ) [ 23 ], 5-hydroxymethyl-2-furancarboxaldehyde ( 8 ) [ 24 ], adenosine ( 9 ) [ 25 ], oxindole ( 10 ) [ 26 ], 3-oxo-4-benzyl-3,4-dihydro-1 H -pyrrolo [2,1-c] oxazine-6-methylal ( 11 ) [ 27 ], 2-methyl-3-pyridinol ( 12 ) [ 28 ], linoleic acid ( 13 ) [ 29 ], oleic acid ( 14 ) [ 30 ], 1(10→6)abeo-ergosta-5,7,9,22-tetraen-11β-methoxy-3α-ol ( 15 ) [ 31 ], citreoanthrasteroid ( 16 ) [ 31 ], 5α,6α-epoxy-3β-hydroxy-(22 E )-ergosta-8(14),22-dien-7-one ( 17 ) [ 32 ], and 7-ketositosterol ( 18 ) [ 33 ] ( Figure 1 ). The UV, HRESIMS, and NMR spectra of compounds 1 – 4 are provided in Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the comprehensive analysis of spectroscopic data from high resolution electrospray ionization mass spectra (HRESIMS), 1D/2D nuclear magnetic resonance (NMR) spectra, ultraviolet (UV) spectra, and comparison with the references, four previously undescribed compounds were named Indusiataines A–D ( 1 – 4 ). Fourteen known compounds were elucidated to be 5-(Methoxymethyl)-1 H -pyrrole-2-carbaldehyde ( 5 ) [ 21 ], nicotinic acid ( 6 ) [ 22 ], dibutyl phthalate ( 7 ) [ 23 ], 5-hydroxymethyl-2-furancarboxaldehyde ( 8 ) [ 24 ], adenosine ( 9 ) [ 25 ], oxindole ( 10 ) [ 26 ], 3-oxo-4-benzyl-3,4-dihydro-1 H -pyrrolo [2,1-c] oxazine-6-methylal ( 11 ) [ 27 ], 2-methyl-3-pyridinol ( 12 ) [ 28 ], linoleic acid ( 13 ) [ 29 ], oleic acid ( 14 ) [ 30 ], 1(10→6)abeo-ergosta-5,7,9,22-tetraen-11β-methoxy-3α-ol ( 15 ) [ 31 ], citreoanthrasteroid ( 16 ) [ 31 ], 5α,6α-epoxy-3β-hydroxy-(22 E )-ergosta-8(14),22-dien-7-one ( 17 ) [ 32 ], and 7-ketositosterol ( 18 ) [ 33 ] ( Figure 1 ). The UV, HRESIMS, and NMR spectra of compounds 1 – 4 are provided in Figure S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the secondary metabolites of natural sources of animals, plants, or microorganisms are still one of the important contents of modern drug research [25–27]. Diterpenoid alkaloids have long attracted the interest of chemists and pharmacologists because of their complex chemical structures and toxicity [7–9, 23, 16, 28–30]. In previous studies, more than 1000 diterpene alkaloids were discovered in Aconitum plants.…”
Section: Discussionmentioning
confidence: 99%
“…It is recorded in “flora of China” as having antispasmodic, analgesic, dispelling wind and dampness, and antipyretic effects [3–5]. However, the root tubers of most aconite plants are highly toxic [6–10], as well as other toxic components [11–12]. So far, More than 1000 diterpene alkaloids have been isolated from the alcoholic or aqueous extracts of the tuberous roots of the aconite plant.…”
Section: Introductionmentioning
confidence: 99%
“…Decoction is one of the oldest and most common forms of administration of herbal medicine in China. Chinese herbs with medicinal properties, such as Aconitum ( Aconitum carmichaeli Debx L.) [ 1 , 2 ] and Nux vomica ( Strychnos nux-vomica L.) [ 3 , 4 ], are often combined to prepare tonics to reduce toxicity and increase effectiveness [ 5 , 6 , 7 ]. Modern science has found that the high temperature and complex chemistry of the decoction process, together with the dissolved secondary metabolites, including small molecules, biological macromolecules and inorganic elements, alter the physicochemical properties of herbal preparations.…”
Section: Introductionmentioning
confidence: 99%